A retrospective cohort study of tamoxifen versus surgical treatment for ER-positive gynecomastia - Weili He; Weidong Wei; Qing Zhang; Rongzhao Lv; Shaohua Qu; Xin Huang; Juan Ma; Ping Zhang; Hening Zhai; Ningxia Wang (BMC Endocrine Disorders, 2023)
Abstract Background Gynecomastia is a common condition in clinical practice. The present study aimed to review the clinical data of ER-positive gynecomastia patients treated by tamoxifen (TAM) versus surgery and discussed the clinical effects of the two treatment strategies. Method We retrospectively collected the clinical indicators of patients with unilateral or bilateral gynecomastia who received treatment at our hospital between April 2018 and December 2021. Depending on the treatment received, the patients were divided into TAM and surgery groups. Result A total of 170 patients were recruited, including 91 patients in TAM group and 79 patients in surgery group. The age of the patients differed significantly between the TAM and surgery groups (P < 0.01). The estrogen level was closer in patients with stable and progressive disease, but significantly different in patients of glandular shrinkage in TAM group (P < 0.01). The proportion of patients achieving stable disease was higher among those with clinical grade 1–2. Among patients classified as clinical grade 3, the proportion of patients achieving glandular shrinkage of the breast was higher after TAM treatment (P < 0.05). The age and length of hospital stay were significantly different in patients undergoing open surgery than minimally invasive rotary cutting surgery and mammoscopic-assisted glandular resection (P < 0.01). Patients had significantly different complications including mild postoperative pain, hematoma, nipple necrosis, nipple paresthesias and effusions among the surgery subgroups (all P < 0.05). The estrogen level and the type of surgery were significantly different between the surgical recurrence and non-recurrence subgroups (P < 0.05). The difference in the thickness of glandular tissues upon the color Doppler ultrasound also reached a statistical significance between the two groups (P = 0.050). An elevated estrogen level was a factor leading to TAM failure. Among surgical patients, the thickness of glandular tissues, estrogen level, and type of surgery performed were risk factors for postoperative recurrence (all P < 0.05). Conclusion Both treatment strategies can effectively treat gynecomastia, but different treatment methods can benefit different patients. TAM treatment is more beneficial than surgery for patients who cannot tolerate surgery, have a low estrogen level, and are clinical grade 1–2. Surgery treatment is better than TAM for patients of clinical grade 3. Different surgery options may lead to different complications. Patients with a greater glandular tissue thickness and a higher estrogen level were shown to have a higher risk of recurrence.